Autism and Emotion: A Narrative Review - Kanagaraj, Sagayaraj; Devishrree, S.; Swetha, J.; Priya, B. Krishna; Sankar, Srivarshini; Cherian, Jincy; Gopal, C.N. Ram; Karthikeyan, S. (Journal of Health and Allied Sciences NU, 2021)
Autism spectrum disorder (ASD) includes a variety of childhood-onset and lifelong neurodevelopmental condition with an enduring impact on multiple domains of functioning characterized by persistent deficits in social communication, restricted and repetitive behavior interest, and activities. They often find it hard to recognize and control emotions but their emotional expression can be improved by various intervention techniques that in turn can help them understand and respond more appropriately to other people. Problems in the area on emotional reciprocity among individual with ASD involve recognizing, understanding, expressing, and regulating emotions. Their ability in emotional reciprocity is often improved with a comprehensive treatment approach, especially by focused emotional enhancement intervention. In this review, we followed the standard IMRAD (Introduction, Methods, Results, and Discussion) structure to critically examine the condition of autism and its relation with genetic mechanism, and how theories of emotion and theory of mind associated with persons with ASD, some of the widely used assessment tools and future research direction in the emotional development of individuals diagnosed with ASD by using the narrative review method. Records collected through research databases such as Scopus, PubMed, Web of Science, Medline, EBSCO and published books with ISBN (International Standard Book Number), and published test manuals were evaluated in-depth and summarized based on the subtopic of the proposed title. A critical theoretical analysis of the genetic mechanism of emotions, theories of emotions, and theory of mind was explained in connection with ASD.
Keywords: autism; emotion; theories of emotion; theory of mind